A nonexistence result for a system of quasilinear degenerate elliptic inequalities in a half-space - Mokthar Kirane; Eric Nabana (Electronic Journal of Differential Equations, 2002)
We show that a system of quasilinear degenerate elliptic inequalities does not have non-trivial solutions for a certain range of parameters in the system. The proof relies on a suitable choice of the test function in the weak formulation of the inequalities.